2013
DOI: 10.1186/1471-2369-14-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oral supplementation with a combination of beta-hydroxy-beta-methylbutyrate, arginine and glutamine on wound healing: a retrospective analysis of diabetic haemodialysis patients

Abstract: BackgroundDiabetes is an important reason for end-stage renal failure and diabetic foot wounds worsen the life qualities of these patients. Protein and amino acid support accelerates the wound healing. The purpose of this retrospective study is to examine the effect of beta-hydroxy-beta-methylbutyrate, arginine and glutamine (Abound®) supplementation on the wound healing.MethodsA total of 11 diabetic dialysis patients were included in this retrospective study aiming to evaluate the effect of the diet support w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 15 publications
2
37
1
3
Order By: Relevance
“…75 Others have demonstrated improved healing in diabetic foot ulcers with supplementation of the diet with arginine. 76 Similar results were found with stasis ulcers. 77 In a randomized controlled trial, Debats et al did not find improved healing with skin graft donor sites in patients who received intravenous supplementation with arginine.…”
Section: Arginine and Glutamine In Wound Healingsupporting
confidence: 73%
“…75 Others have demonstrated improved healing in diabetic foot ulcers with supplementation of the diet with arginine. 76 Similar results were found with stasis ulcers. 77 In a randomized controlled trial, Debats et al did not find improved healing with skin graft donor sites in patients who received intravenous supplementation with arginine.…”
Section: Arginine and Glutamine In Wound Healingsupporting
confidence: 73%
“…The mixture of arginine, glutamine, and HMB has been studied for its influence on wound healing in 3 different trials 8 , 9 . These 3 studies reported that this mixture increased collagen accumulation in elderly subjects and also enhanced the healing of diabetic foot ulcers 8 , 9 , 13 . Supplementation with this amino acid mixture for 2 weeks resulted in an increase in hydroxyproline accumulation in subcutaneously placed polytetraflouroethylene tubes in healthy elderly volunteers in one of these studies 8 .…”
Section: Discussionmentioning
confidence: 97%
“…One was a retrospective review of 11 diabetic patients with foot ulcers who were given supplementation with arginine, glutamine, and HMB. In those 11 patients who were evaluated, degeneration was not identified in any wounds assessed with standardized scoring systems for wound depth and wound appearance [6], but on the contrary, statistically significant improvements in scores for wound depth and wound appearance were identified. This implies a decrease in diabetic wound catabolism leading to diminished wound degeneration.…”
Section: Literature Review: Pilot Data In Contextmentioning
confidence: 86%
“…These particular MeSH search terms identified only two sources as investigating dietary amino acid supplementation in patients with diabetic foot ulcers [6,7].…”
Section: Methodsmentioning
confidence: 99%